2009
DOI: 10.1097/ijg.0b013e3181996f05
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disk Size Variability Between African, Asian, White, Hispanic, and Filipino Americans Using Heidelberg Retinal Tomography

Abstract: Purpose-To compare the optic disk size of African, Asian, Caucasian, Hispanic and Filipino American patients in a multiethnic glaucoma practice.Patients and Methods-576 eyes of 319 patients who had consecutively received Heidelberg Retinal Tomography II (HRT) from February 2006 to October 2007 in a glaucoma clinic that met inclusion criteria were included. The five ethnic groups represented were Caucasian (n = 215, 37.3%), Asian (non-Filipino) (n = 178, 30.8%), African (n = 67, 11.6%), Hispanic (n = 66, 11.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 33 publications
8
40
1
1
Order By: Relevance
“…It has been reported that the optic disc size in Asian eyes is larger than that in white Americans. 21,22 Similarly, the disc area (1.93 vs. 1.83 mm 2 ) was larger for normal subjects in our study compared with normal subjects in the article by Mwanza et al, 15 whereas the rim area was similar (1.3 vs. 1.27 mm 2 ). Rao et al 23 found that optic disc size did not influence any of the scanning protocols in spectral-domain OCT (RTVue; Optovue, Inc., Fremont, CA) but the sensitivity of the rim area increased and the specificity decreased with larger optic discs.…”
Section: Discussionsupporting
confidence: 49%
“…It has been reported that the optic disc size in Asian eyes is larger than that in white Americans. 21,22 Similarly, the disc area (1.93 vs. 1.83 mm 2 ) was larger for normal subjects in our study compared with normal subjects in the article by Mwanza et al, 15 whereas the rim area was similar (1.3 vs. 1.27 mm 2 ). Rao et al 23 found that optic disc size did not influence any of the scanning protocols in spectral-domain OCT (RTVue; Optovue, Inc., Fremont, CA) but the sensitivity of the rim area increased and the specificity decreased with larger optic discs.…”
Section: Discussionsupporting
confidence: 49%
“…Asian eyes show several structural differences compared to Caucasian eyes [27][28][29][30][31], which may influence the clinical value of the OCT parameters even when highly myopic eyes are excluded from the analysis. This suggests that no structural parameter developed for Asian eyes can automatically be applied to other ethnic groups in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…They found that G/ T ratio decreases already in the early stages of glaucoma, and the AUROC of the G/T ratio is significantly higher than circumpapillary RNFL thickness parameters in Japanese primary open angle glaucoma eyes [26]. Asian eyes, however, differ from those of other ethnic groups in several respects including disc size and axial length [27][28][29][30][31]. For G/T ratios to be considered as a generally useful parameter of structural glaucoma diagnostics, they need to be consistent across races and ethnic groups.…”
Section: Introductionmentioning
confidence: 93%
“…63 Candidate pathophysiological theories for the earlier and more severe presentation of glaucoma in patients of African ancestry include: larger optic disc size (which mechanically increases posterior bowing of the lamina cribrosa at any given IOP), lower posterior scleral compliance (which reduces deformability of the optic nerve at its exit point at the lamina cribrosa), lower corneal hysteresis (which reflects reduced corneal energy-dampening capacity and may correlate with reduced overall distensibility of glaucomatous eyes), shorter trabecular meshwork height (which may anatomically contribute to reduced aqueous outflow particularly in conjunction with aging-related changes in the trabecular meshwork and anterior chamber angle), and lower retinal blood flow (which increases susceptibility to ischemia-related etiologies of retinal ganglion cell loss). [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] In concert with these parameters, elevated IOP is a welldocumented risk factor for progressive VF field loss or presentation with advanced glaucoma among patients of many ancestries. [81][82][83][84][85] The association of AT6 with elevated current IOP in our study may reflect some combination of physiological barriers to IOP control and socioeconomic barriers to glaucoma treatment adherence.…”
Section: Section 32 Visual Field Characteristicsmentioning
confidence: 99%